Creative Biblical exegesis : Christian and Jewish hermeneutics through the centuries - Uffenheimer, Benjamin; Reventlow, Henning Graf (Journal for the study of the Old Testament. Supplement series ;, 1988)
These papers were presented to a unique conference held in Israel in December 1985, sponsored by Tel Aviv University and the University of Bochum in the Federal Republic of Germany. Discussion of Christian and Jewish exegesis in historical perspective was not only mutually illuminating, but also laid the foundations for a new level of Jewish-Christian dialogue. The papers presented in this volume are: H. Graf Reventlow, Humanist Exegesis: The famous Hugo Grotius. Y. Hoffman, The Technique of Quotation as an Interpretative Device. D. Flusser, Past and Future according to the Creative Exegesis o.